Allusions to Dostoevsky in Yury Buida’s Stories - Oksana Vasilievna Sizykh, Olga Vladimirovna Dediukhina, (Opción, 2019)
The article demonstrates the continuity of the main thematic and ideological corpus of Dostoevsky’s novels, as well as elements of poetics in Yury Vasilyevich Buida’s short story collection Jungle via comparative qualitative research methods. As a result, the conceptual character of the author’s opposition of light/darkness, realizes the ideas of both writers about the nature of the world and humanity. In conclusion, an important aspect of the research is the continuity between the works of Buida and those of Dostoevsky, which stems from common cultural elements and historical features of Russian society.